Problematika Keterlambatan Penyampaian Tanggapan SP2DK Wajib Pajak yang di terbitkan oleh KPP Pratama di kota Pontianak - Aswat, Ibnu (LPPM UBP, 2024)
SP2DK is a letter from the Tax Office Director (KPP) issued to taxpayers to explain data and/or information regarding the suspected non-fulfillment of tax obligations in accordance with the provisions of tax legislation. The term SP2DK, commonly referred to as the